Between Protection and Bondage: The Paradox of Kafāla in Saudi Arabia and Italy - Vasco Fronzoni; Michel Emi Maritato (Qiyam Islamic Studies Center Foundation, 2026)
This article investigates the contemporary application of kafāla as a legal instrument for the protection of vulnerable individuals particularly women and minors through a comparative analysis between Saudi Arabia and Italy. While kafāla originates in Islamic law as a mechanism of guarantee, care and social responsibility, its modern implementation reveals significant divergences between normative ideals and practical realities. This research adopts a set of normative and functional criteria. It analyses the effectiveness of enforcement mechanisms through inspection systems, sanctions against abuses and the practical enforceability of rights. Indeed, the study adopts a qualitative, documentary, and thematic approach to analyze Islamic law and ethics grounded in maqāṣid al-sharīʿa by examining primary sources, legislation, and case law to understand their normative application to contemporary issues, with a comparative focus between Saudi Arabia and Italy. In the Kingdom of Saudi Arabia, kafāla works quite effectively with vulnerable minors. However, it is with the specific category of foreign domestic workers that the legal instrument experiences a short circuit, failing to achieve its Shariatic objectives. Conversely, in Italy, a secular country with a non-Muslim majority and a Catholic influence, where the application of canon law is limited and the systematic application of Islamic law is only sporadic, positive experiences are emerging, thanks to case law. In Saudi Arabia, especially within the context of migrant domestic work, kafāla has been progressively distorted into an instrument of structural dependence, often facilitating exploitation, isolation and legal vulnerability. Despite recent regulatory reforms, the lack of effective enforcement mechanisms continues to undermine the protective function that Islamic legal ethics originally attributed to this institution. Conversely, in Italy, a positive legal system initially reluctant to recognize kafāla, jurisprudence has progressively reinterpreted it in light of the best interests of the child and international child protection standards. Through this judicial evolution, kafāla has been revitalized as a functional tool of protection for abandoned and unaccompanied minors. This normative paradox illustrates how legal institutions are not inherently protective or oppressive, but depend on the interpretative, cultural and institutional frameworks within which they operate.